Model hubungan kinerja ESG, struktur modal, dan profitabilitas - Amelia Oktrivina (Jurnal STEI Ekonomi, 2025)
This study examines the relationship between capital structure and ESG performance, along with the moderating role of profitability, using a sample of 30 publicly listed companies on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Through path analysis and Moderated Regression Analysis (MRA), we find that Debt-to-Asset Ratio (DAR) positively influences ESG performance, suggesting that firms with higher leverage tend to achieve better ESG scores. However, this relationship is conditional on the type and level of profitability. Return on Equity (ROE) and Earnings Per Share (EPS) emerge as significant positive moderators, enhancing the positive effect of DAR on ESG performance. In contrast, Net Profit Margin (NPM) shows no moderating effect, while Operating Profit Margin (OPM) directly improves ESG performance without significantly moderating the DAR-ESG link. These findings highlight that not all profitability metrics equally influence the capital structure-ESG relationship. Practically, the study suggests that sustainable financing strategies should consider both leverage levels and profitability types—firms with high ROE or EPS can more effectively utilize debt to support ESG initiatives, whereas low-profitability firms should exercise caution to avoid compromising their sustainability commitments. This research provides valuable insights for corporate management and policymakers in aligning financial strategies with ESG objectives.